Ortaçağ Avrupası’nda bir düalist heretik hareket olarak “Katarlar” - Uzunoğlu, Feyza (My University, 2010)
Katarlar XII. ve XIII. yy’larda Kuzey İtalya ve Güney Fransa(Languedoc)’da etkili olmuş heretik bir Hıristiyan mezhebidir. Katarların kökeni konusunda diğer düalist heretiklerden geldiği ya da kendi merkezinde ortaya çıktığına dair iki farklı görüş mevcuttur. Öte yandan Katarlara atfedilen heretik tanımı Katolik Kilise’sine göre heretik olmalarını ifade etmektedir. Zira Katarlar evharistiya, haç, Tanrının ve İsanın tabiatı, yaratılış ve ahiret inancı gibi itikâdî ve amelî pek çok konuda Katolik Kilisesi’ne aykırı düşen Katarlara Katolik Kilisesi tepki göstermiştir. Önce Kilise babalarının reddiye ve vaazları, Katar din adamlarıyla yapılan açık oturumlar gibi hafif tedbirler alınmıştır. Engizisyon Mahkemelerinde pek çok Katar diri diri yakılarak Katar doktrini tarihten tamamen silinmiştir. Katarlar, Düalizm, Heretiklik, Engizisyon, Haçlı Seferleri, Katolik Kilise Tarihi ve Teolojisi.

The cathars are a heretical Christian sect that influenced in North Italy and South France(Languedoc) in XII and XIIth centuries. There are two views about the appereance of the sect: One of them is that it came from the other dualist heretical Christian traditions, the other one is that it was a self-centering sect. On the other hand, the heretic definition that is imputed to the Cathars expresses being heretical according to the Catholic Church. Since Cathars rejects lots of doctrins and practices of the Catholic Church such as: the eucharist, cross, the nature of the God and the nature of Jesus, the belief of creation and the hereafter. Catholic Church firstly take measures with the preaches and the polemical works of Church fathers and arranged panels with the Religious men of Cathars. The cathar doctrine was went out of existence after thousands of cathars were burned alive in Inqusition. Key words: Cathars, Dualism, Heresy, Inquisition, Crusades, Catholic Church History and Catholic Theology.
Keywords: Felsefe; Ortaçağ_Felsefe